Behavioral and psychological symptoms of dementia and Alzheimer’s disease progression in Down syndrome - Melissa R. Jenkins; Jamie C. Peven; Lauren Kubic; Benjamin L. Handen; Sharon J. Krinsky-McHale; Christy L. Hom; Alice Lee; Dana L. Tudorascu; Max McLachlan; Matthew Zammit; Davneet Minhas; Weiquan Luo; et al. (Journal of Neurodevelopmental Disorders)
Abstract Background Adults with Down syndrome (DS) have a 90% lifetime risk for Alzheimer’s disease (AD), with neurobiological pathology present decades prior to dementia onset. The profile and timing of cognitive decline in DS is well-documented. However, there is a small body of research on whether Behavioral and Psychological Symptoms of Dementia (BPSD) occur early on in the progression of AD in DS and are associated with early AD pathology (i.e., amyloid-beta [Aβ] and neurofibrillary tau tangles [NFT]). Methods Data were analyzed from 337 adults with DS (M = 45.13 years, SD = 9.53 years) enrolled in a large cohort study. The Reiss Screen for Maladaptive Behavior (RSMB) measured common behaviors reported in BPSD across up to four study cycles (spaced approximately 16 months apart). Linear mixed models estimated change in BPSD as predicted by baseline (a) dementia status (i.e., cognitively stable, mild cognitive impairment [MCI], or dementia), (b) Aβ positron emission tomography (PET) tracer [11C] PiB, and (c) NFT PET tracer [18F]AV-1451. Models controlled for chronological age, sex, study site, premorbid intellectual disability level, APOE e4 allele carrier status, psychiatric diagnoses, and psychiatric medication use. Results Compared to cognitively stable participants, participants whose status was MCI or dementia, had significantly higher baseline RSMB subdomain scores. Increases in RSMB Depression-Behavioral, Depression-Physical, and Psychosis were observed for participants with MCI. Higher baseline Aβ and NFT were associated with higher RSMB Avoidant at baseline, and increases in RSMB Depression-Physical and Psychosis over time. Conclusions BPSD are an important part of AD in DS, particularly during the prodromal stage. Elevated Aβ and NFT predict higher initial avoidance and change in physical depression behaviors and may indicate MCI in adults with DS. Broader increases in BPSD are observed as adults with DS progress from early to late-stage dementia. Clinicians should rule out other possible causes of BPSD when screening for AD, such as stressful life experiences or co-occurring medical conditions. Caregivers of adults with DS should have resources on BPSD management and self-care strategies.